A Qualitative Study of the Experience of Immediate Antiretroviral Therapy Among Urban Persons With Newly Diagnosed Human Immunodeficiency Virus. (17th September 2021) - Christopoulos, Katerina A; Erguera, Xavier A; VanderZanden, Lyndon; Campbell, Chadwick; Green, Maya; Tsuzuki, Manami Diaz; Schneider, John; Coffey, Susa; Bacon, Oliver; Gandhi, Monica; Koester, Kimberly A
Abstract: Background: Guidelines recommend immediate antiretroviral therapy (ART) at or shortly after human immunodeficiency virus (HIV) diagnosis, yet little is known about how people living with HIV (PLWH) experience this treatment strategy, including racial/ethnic minorities, cisgender/transgender women, and those with housing instability. Methods: To assess the acceptability of immediate ART offer among urban PLWH, understand how this approach affects the lived experience of HIV diagnosis, and explore reasons for declining immediate ART, we conducted a cross-sectional qualitative study using semi-structured interviews with individuals who had been offered immediate ART after HIV diagnosis at a safety-net HIV clinic in San Francisco and a federally qualified health center in Chicago. Interviews were analyzed using thematic analysis. Results: Among 40 participants with age range 19–52 years, 27% of whom were cisgender/transgender women or gender-queer, 85% racial/ethnic minority, and 45% homeless/unstably housed, we identified 3 major themes: (1) Individuals experienced immediate ART encounters as supportive; (2) individuals viewed immediate ART as sensible; and (3) immediate ART offered emotional relief by offsetting fears of death and providing agency over one's health. Reasons for declining immediate ART ranged from simply needing a few more days to complex interactions of logistical and psychosocial barriers. Conclusions: Immediate ART was highly acceptable to urban persons with newly diagnosed HIV infection. Immediate ART was viewed as a natural next step after HIV diagnosis and provided a sense of control over one's health, mitigating anxiety over a decline in physical health. As such, immediate ART somewhat eased but in no way obviated the psychosocial challenges of HIV diagnosis.